Застосування ігрових технологій на уроках у початкових класах - Алендарь, Надія; Alendar’, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлено теоретичні аспекти застосування ігрових технологій у навчально-виховному процесі початкової школи. Визначено роль та обґрунтовано доцільність використання ігрових технологій у навчанні молодших школярів. Розглянуто спектр цільових орієнтацій ігрової технології та охарактеризовано особливості та структуру ігрових технологій. The problem of the child’s education according to personal-oriented approach did the change of the priority objectives of primary school. In the work with primary school pupils is necessary to introduce active forms and teaching methods. They take the important place. The playing technologies are the unique learning form that allows to make the playing technology interesting and exciting for younger students. Using playing technology in the teaching primary school children directs at improving the quality of education, the development of cognitive activity and creative individuality of pupils. In the article clarified the theoretical aspects of playing technologies in the educational process of elementary school. The role was determined and the feasibility of using playing technology was proved in the teaching of children in primary school. The spectrum of specific orientations of the playing technology was examined and the peculiarities of application of playing technology in the classroom in elementary school have characterized.
Use the playing technologies at the primry school’s classes
Keywords: педагогічна технологія; технологія навчання; гра; ігрові технології; учні молодших класів; pedagogic(al) technology; teaching technology; game; playing technology; primary school pupils